Gamification in Education: Innovative Solutions through Learning System Development to Increase Student Motivation and Interest - Lilis, Erlin; Indriyani, Laila; Azzahra, Putri Delarani; Purwani, Fenny (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Gamification in education is an innovative solution to increase student motivation and engagement. This research aims to develop an interesting and interactive gamification-based learning system. The method used is Feature Driven Development (FDD), which supports application development in stages and iteratively. With FDD, features such as points, levels, challenges and rewards are integrated into the application, allowing for adaptation to evolving needs. The research results show that the application of gamification in e-learning has succeeded in increasing student interest and participation. Through leaderboards and badges, students are encouraged to compete and achieve achievements. Interactive narratives at each level and quest features strengthen students' emotional involvement in learning. In addition, gamification overcomes the shortcomings of traditional learning methods which are often monotonous. The implementation of gamification creates a learning experience that is both fun and challenging. Students are more motivated to complete learning assignments and actively participate in class discussions.